(untitled) (Nexo Revista Científica, 2021)
This article explores the origins of Chemical Engineering. It deals mostly with the emergence of the Chemical Engineering concept, the recognition of the field as an independent discipline, and its initial development. Although the conception of Chemical Engineering takes place in Great Britain, the discipline developed primarily in the United States, where it soon took the form in which we know it today. Two decades after its conception, the new discipline found its place in Latin American universities (Chile, Argentina). The discipline and profession developed as the industry itself grew rapidly, in response to a growing demand from society for the products of the chemical industry. The creation of Chemical Engineering as an academic programme was consolidated and was offered in many countries, both in those with a tradition in education in the area, and in others where the programme was a novelty.